Probabilistic assessment of loss in revenue generation in demand-driven production - Hussain, Omar; Dillon, Tharam; Hussain, Farookh Khadeer; Chang, Elizabeth (Chapman & Hall, 2011)
In Demand-driven Production with Just-in-Time inputs, there are several sources of uncertainty which impact on the manufacturer’s ability to meet the required customer’s demand within the given time frame. This can result in a loss of revenue and customers, which will have undesirable impacts on the financial aspects and on the viability of the manufacturer. Hence, a key concern for manufacturers in just-in-time production is to determine whether they can meet a specific level of demand within a given time frame, to meet the customers’ orders and also to achieve the required revenue target for that period of time. In this paper, we propose a methodology by which a manufacturer can ascertain the probability of not meeting the required demand within a given period by considering the uncertainties in the availability of production units and raw materials, and the loss of financial revenue that it would experience as a result.